Traditional Uses of Animals in the Himalayan Region of Azad Jammu and Kashmir - Faiz, Maryam; Altaf, Muhammad; Umair, Muhammad; Almarry, Khalid S.; Elbadawi, Yahya B.; Abbasi, Arshad Mehmood (Frontiers in Pharmacology, 2022)
Background: The use of animals and animal-derived products in ethnopharmacological applications is an ancient human practice that continues in many regions today. The local people of the Himalayan region harbor rich traditional knowledge used to treat a variety of human ailments. The present study was intended with the aim of examining animal-based traditional medicine utilized by the population of the Himalayan region of Azad Jammu and Kashmir. Methods: Data was collected from 2017 to 2019 through individual and group interviews. Data on ethnopharmacological uses of animal products were analyzed utilizing following indices such as frequency of citation, use-value, relative importance, similarity index, principal component analysis and cluster analysis to find the highly preferred species in the area. Results: Ethnopharmacological applications of 62 species of vertebrates and invertebrates were documented. Flesh, fat, bone, whole body, milk, skin, egg, head, feathers, bile, blood, and honey were all used in these applications. The uses of 25 animals are reported here for the first time from the study area (mainly insects and birds, including iconic species like the kalij pheasant, Lophura leucomelanos; Himalayan monal, L. impejanus; and western tragopon, Tragopan melanocephalus). The diversity and range of animal-based medicines utilized in these communities is an indication of their strong connections with local ecosystems. Conclusion: Our results provide baseline data valuable for the conservation of vertebrate and invertebrate diversity in the region of Himalayan of Azad Jammu and Kashmir. It is possible that screening this fauna for medicinally active chemicals could contribute to the development of new animal-based drugs.